Phenolic Compounds and Antioxidant Activities of Skins and Seeds of Foreign and Iranian Grapes - Neshati; F. Rahmani; H. Doulati-Baneh (Journal of Pharmacy and Nutrition Sciences, 2014)
Grape skins and seeds are sources of phenolic compounds that contribute to the sensory characteristics and beneficial bioactivity of wines and other processed foods. Grape seed and skin extracts from foreign, wild and Iranian cultivars were assayed for their antioxidant properties and phenolic compositions. Finally, the results were compared with those of Vitis vinifera cv. Muscat of Alexandria and V.labrusca. Among the skins of grape cultivars analyzed, those of Lalsiyah contained the highest amount of total phenolics (1067.5 mg 100g-1 gallic acid equivalent of fresh weight) and antiradical activities (0.79 m mol g-1 trolox equivalent of fresh weight). In contrast, Dedeskiramfi contained highest amount of seed total phenolics (2277.3 mg 100 g-1 GAE of fresh weight). The phenolic content of different grapes depends mainly on the grape skin color. The total phenolic content of W8 and W11 with white skins was significantly different from grapes with dark skins. Lalsiyah skin contained the highest amount of total flavonoid, total anthocyanins content, total procyanidin monomers and antiradical activity. Since, total phenolic content is an index of potent antioxidant capability; Lalsiyah will be good resource of antioxidant in food and pharmaceutical industries.